Surgical Anatomy of the Retrosigmoid Approach with Endoscopic-Assisted Reverse Anterior Petrosectomy: Optimizing Meckel's Cave Access from the Posterior Fossa - De Bonis, Alessandro; Torregrossa, Fabio; Dang, Danielle D.; Leonel, Luciano César P. C.; Mortini, Pietro; Link, Michael; Colin, Driscoll; Peris-Celda, Maria (Journal of Neurological Surgery Part B: Skull Base, 2024)
We investigated the extent of access to Meckel's cave (MC) and the middle cranial fossa (MCF) protecting the internal carotid artery (ICA) using the retrosigmoid approach with endoscopic-assisted reverse anterior petrosectomy (EA-RAP).Five specimens were dissected using the limited and extended EA-RAP. Based on the bone removal of the internal acoustic meatus (IAM) and subarcuate fossa, exposure of the MC and ICA were statistically compared.The limited and extended EA-RAP allowed access to the medial and anterior MC (4 mm posterior to the first genu of the cavernous ICA, and 20 mm posterior to foramen rotundum [FR]). The access to the lateral MC varied with distance of 12 and 8 mm medial to the foramen ovale for the limited and extended EA-RAP, respectively.In the extended EA-RAP, the exposure of the ICA was gained by drilling with the 0-degree endoscope (3 mm) versus 45-degree endoscope (9 mm). The working distances from the midpoint of the IAM to the most medial point of the exposed ICA was 24 mm. The most lateral point of the exposed ICA varied between 0- and 45-degree endoscopes with a distance of 21 and 13 mm, respectively.A coronal plane from the posterior genu of the cavernous ICA and a sagittal plane to the common crus of the semicircular canals can define the area of MCF accessed by the EA-RAP. Drilling of the temporal bone should be carefully customized according to the patient and can be aided by endoscopic assistance for direct visualization to minimize the risk of injuries to ICA.
Keywords: RAP; EA-RAP; retrosigmoid intradural suprameatal approach; RISA; Meckel's cave; petrous internal carotid artery; retrosigmoid; reverse anterior petrosectomy; suprameatal tubercle